2013 6th International IEEE/EMBS Conference on Neural Engineering (NER) 2013
DOI: 10.1109/ner.2013.6696042
|View full text |Cite
|
Sign up to set email alerts
|

Specific absorption rate in a standard phantom containing a Deep Brain Stimulation lead at 3 Tesla MRI

Abstract: Finite elements methods (FEM) simulations are presented showing the specific absorption rate (SAR) distribution in the case of a Deep Brain Stimulation (DBS) lead inside a standard phantom exposed to 128 MHz / 3 Tesla magnetic resonance imaging (MRI). The electromagnetic model is proposed as a tool to study the safety of patients with an implanted DBS lead undergoing clinical 3T MRI systems. The simulations were based on an electromagnetic and circuit cosimulation methodology and allowed for fine tuning of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…A numerical model of a shielded highpass birdcage head coil (see Supplementary Table S1) was implemented and tuned to the 1.5 T with a Larmor frequency of 64 MHz (Figures 3A,B). The numerical head coil matched the coil used in the measurements (Bonmassar et al, 2013), and the geometry consisted of two end rings, which were connected through 16 rungs. The material used for modeling the rings of the head coil as well as the shield was copper.…”
Section: Simulations (Numerical)mentioning
confidence: 99%
“…A numerical model of a shielded highpass birdcage head coil (see Supplementary Table S1) was implemented and tuned to the 1.5 T with a Larmor frequency of 64 MHz (Figures 3A,B). The numerical head coil matched the coil used in the measurements (Bonmassar et al, 2013), and the geometry consisted of two end rings, which were connected through 16 rungs. The material used for modeling the rings of the head coil as well as the shield was copper.…”
Section: Simulations (Numerical)mentioning
confidence: 99%
“…Two sets of simulations were performed using ANSYS Electronics Desktop. The 3T birdcage coil model was implemented using electromagnetic and circuit cosimulation [13], while the phantom models require only electromagnetic simulation. After solving the 3T birdcage coil model, the incident field was linked to a model including the CHM within the bore.…”
Section: Mri Birdcage Coil Modelmentioning
confidence: 99%
“…20,21 This effect has been characterized in multiple experimental and simulation studies. [22][23][24][25][26][27][28][29][30][31][32][33][34][35] Parallel transmission (pTx) has been proposed to mitigate this problem because pTx coils and pulses offer additional transmit degrees of freedom that can be used to shape the B + 1 distribution, which controls the flip angle (FA); as well as electric fields (E-field) induced in the patient, which cause heating. For example, Etezadi-Amoli et al built a 4-channel planar pTx system and showed that it is possible to generate transmit waveform combinations minimizing the current induced in a guidewire equipped with a current sensor.…”
Section: Introductionmentioning
confidence: 99%